2015
DOI: 10.1002/sdtp.10543
|View full text |Cite
|
Sign up to set email alerts
|

Paper No S16.1: SVGA Bidirectional OLED Microdisplay for Near‐to‐Eye Projection

Abstract: The bidirectional microdisplay approach combines organic light-emitting diode (OLED) image display and silicon complementary metal-oxide-semiconductor image sensing in a single chip. Its application in smart glasses might enable gaze-controlled interaction. This is to present a new bidirectional OLED microdisplay featuring super video graphics array resolution for both image display and acquisition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…For example, separate light-detective and photoemissive devices were combined into a single system that can perform both photoresponse and electroluminescence. As per our literature survey, there are only a few published reports on light-emitting phototransistors upconverting infrared light into visible light fabricated by direct combination of an inorganic photodetector and an organic light-emitting diode. However, not only do these designs require multiple devices and a cumbersome fabrication process, but also the reported external quantum efficiency (EQE) is not high. , Notably, Oh et al . demonstrated light-responsive LEDs by using double-heterojunction nanorods (DHNRs), which can separate the photogenerated excitons and radiative recombination of excitons within a single device .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, separate light-detective and photoemissive devices were combined into a single system that can perform both photoresponse and electroluminescence. As per our literature survey, there are only a few published reports on light-emitting phototransistors upconverting infrared light into visible light fabricated by direct combination of an inorganic photodetector and an organic light-emitting diode. However, not only do these designs require multiple devices and a cumbersome fabrication process, but also the reported external quantum efficiency (EQE) is not high. , Notably, Oh et al . demonstrated light-responsive LEDs by using double-heterojunction nanorods (DHNRs), which can separate the photogenerated excitons and radiative recombination of excitons within a single device .…”
mentioning
confidence: 99%
“…4−6 However, not only do these designs require multiple devices and a cumbersome fabrication process, but also the reported external quantum efficiency (EQE) is not high. 6,7 Notably, Oh et al demonstrated light-responsive LEDs by using doubleheterojunction nanorods (DHNRs), which can separate the photogenerated excitons and radiative recombination of excitons within a single device. 1 However, the reported device used complicated fabrication techniques, raising concerns about cost-effectiveness, reliability, reproducibility, and durability.…”
mentioning
confidence: 99%
“…4a). Alternatively, a bidirectional Fraunhofer display of the same size was used 55 (Extended Data Fig. 4b).…”
Section: Optical Designmentioning
confidence: 99%
“…Organic light emitting diodes (OLEDs) integrated with photovoltaic device in a tandem structure provides a new application of portable display and ecofriendly devices . Although the pursuit of optoelectronic integration leads to an increase in device functionality and an improvement in performance, the manufacturing for a series of monofunctional components and then integrating them into a system will definitely increase fabrication complexity as well as product costs . Therefore, to achieve an individual component that equipped with multiple functions is highly desirable, which can simplify the fabrication process, reduce manufacturing costs, boost the integration level, and expand possible application fields.…”
Section: Introductionmentioning
confidence: 99%